Investment Ability as a Source of the Company’s Competitive Advantage Based on Human and Financial Resources-Theoretical Outline - Bukvič, Vladimir (Archives of Business Research, 2023)
In this paper, which is based on extensive research, the author provides a theoretical outline of the investment ability of companies. He understands investment ability as a type of knowledge that is necessary before the investment itself and also for its implementation. Investment ability is the ability of companies to correctly assess the feasibility and profitability of an investment project, and to define its detailed specifications, the required technology and the most favorable sources of financing, both internal and external. The purpose of this paper is to fill a gap in the field of studying the relationship between resources and investment ability. The author defines investment ability as a relatively new theoretical construct, from the point of view of resource-based theory. The aforementioned theory focuses on the company’s resources and dynamic capabilities and thus offers a suitable theoretical basis for determining how internal factors, which are also observed in the field of the company’s investment activity and which in a way help define its investment ability, represent a source of competitive advantage. In addition to the theoretical definition of a company’s investment ability, the aim of the author’s contribution is to investigate whether it is possible and feasible in practice to develop and/or adapt an instrument for measuring investment ability. Based on a thorough study of human and financial resources as key to defining investment ability, the author identifies a potential set of variables or indicators that can be used to assess and measure the investment ability of companies. The author included these measurement variables in the conceptual model of investment ability, which he developed and tested on the example of Slovenian companies.